E-KKN Tematik Universitas Muhammadiyah Enrekang: Pengabdian Kepada Masyarakat dalam Bidang Pendidikan dan Kesehatan di Desa Pasang Kecamatan Maiwa - Ilham Assidiq; Dian Firdiani; Umiyati Jabri; Ita Sarmita Samad; Muh. Yunus Sudirman; Muh.Idham Halik; Elihami Elihami; Nur Atiqa; Firmansyah Firmansyah; Alhafri Alhafri; Widya Widya; Wisnah Wisnah (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
The Real Work Lecture (E-KKN) activity was carried out by UNIMEN students on 2 August-10 September 2021, in Pasang Village, Maiwa District, Enrekang Regency. The purpose of this KKN activity is to serve and be directly involved with the community through activities that have been previously designed to be carried out. Methods Data collection was carried out by interviews and observations in the community. The results of the activities that have been carried out in the implementation of this E-KKN are (1) The E-KKN program proposed by E-KKN students is very much supported by the village of Pasang and the local community. (2) Through the E-KKN program this is one of the considerations in exploring the potentials that exist in the village and have not been managed properly. (3) With the E-KKN it provides benefits for all parties, be it students, villages and the community